2001
DOI: 10.1007/s004640000294
|View full text |Cite
|
Sign up to set email alerts
|

Preinsertion local anesthesia at the trocar site improves perioperative pain and decreases costs of laparoscopic cholecystectomy

Abstract: Preinsertion of local anesthesia at the trocar site in laparoscopic cholecystectomy significantly reduces postoperative pain and decreases medication usage costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 6 publications
2
33
0
3
Order By: Relevance
“…There are various methods of using local anaesthetic to reduce post-operative pain like infiltration at trocar site to reduce somatic pain, in gall bladder fossa for reducing visceral pain, in sub diaphragmatic areas to reduce referred pain to shoulders. 5,6 These agents reduce pain by reversibly decreasing the rate of depolarisation and repolarisation of excitable membranes. 7 It is important that the local infiltration of long-acting anesthetic be made before giving incision.…”
Section: Discussionmentioning
confidence: 99%
“…There are various methods of using local anaesthetic to reduce post-operative pain like infiltration at trocar site to reduce somatic pain, in gall bladder fossa for reducing visceral pain, in sub diaphragmatic areas to reduce referred pain to shoulders. 5,6 These agents reduce pain by reversibly decreasing the rate of depolarisation and repolarisation of excitable membranes. 7 It is important that the local infiltration of long-acting anesthetic be made before giving incision.…”
Section: Discussionmentioning
confidence: 99%
“…7 Hasaniya et al studied the effect of preincisional bupivacaine instillation and concluded that the mean pain scores were lower as compared to controls at 4 th and 24 th hour postoperatively. 8 Conflicting results have been reported by Ke et al stating that the popular practice of infiltrating bupivacaine at time of incision closure does not offer any benefit in the control of pain after laparoscopy. 9 A Cochrane review was published in 2014 in the wiley online library, reviewing a total of 26 papers on grounds of wound infilitration with local anaesthetics for laparoscopic cholecystectomies.…”
Section: Vas Scoresmentioning
confidence: 99%
“…In addition, the number of times and amount of analgesia was administered was not mentioned (24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%